Streptococcal Extracellular Membrane Vesicles Are Rapidly Internalized by Immune Cells and Alter Their Cytokine Release - Mehanny, Mina; Koch, Marcus; Lehr, Claus-Michael; Fuhrmann, Gregor (Frontiers in Immunology, 2020)
Extracellular vesicles are membranous structures shed by almost every living cell. Bacterial gram-negative outer membrane vesicles (OMVs) and gram-positive membrane vesicles (MVs) play important roles in adaptation to the surrounding environment, cellular components' exchange, transfer of antigens and virulence factors, and infection propagation. Streptococcus pneumoniae is considered one of the priority pathogens, with a global health impact due to the increase in infection burden and growing antibiotic resistance. We isolated MVs produced from the S. pneumoniae reference strain (R6) and purified them via size exclusion chromatography (SEC) to remove soluble protein impurities. We characterized the isolated MVs by nanoparticle tracking analysis (NTA) and measured their particle size distribution and concentration. Isolated MVs showed a mean particle size range of 130–160 nm and a particle yield of around 1012 particles per milliliter. Cryogenic transmission electron microscopy (cryo-TEM) images revealed a very heterogeneous nature of isolated MVs with a broad size range and various morphologies, arrangements, and contents. We incubated streptococcal MVs with several mammalian somatic cells, namely, human lung epithelial A549 and human keratinocytes HaCaT cell lines, and immune cells including differentiated macrophage-like dTHP-1 and murine dendritic DC2.4 cell lines. All cell lines displayed excellent viability profile and negligible cytotoxicity after 24-h incubation with MVs at concentrations reaching 106 MVs per cell (somatic cells) and 105 MVs per cell (immune cells). We evaluated the uptake of fluorescently labeled MVs into these four cell lines, using flow cytometry and confocal microscopy. Dendritic cells demonstrated prompt uptake after 30-min incubation, whereas other cell lines showed increasing uptake after 2-h incubation and almost complete colocalization/internalization of MVs after only 4-h incubation. We assessed the influence of streptococcal MVs on antigen-presenting cells, e.g., dendritic cells, using enzyme-linked immunosorbent assay (ELISA) and observed enhanced release of tumor necrosis factor (TNF)-α, a slight increase of interleukin (IL)-10 secretion, and no detectable effect on IL-12. Our study provides a better understanding of gram-positive streptococcal MVs and shows their potential to elicit a protective immune response. Therefore, they could offer an innovative avenue for safe and effective cell-free vaccination against pneumococcal infections.